2010
DOI: 10.1097/ta.0b013e3181e51211
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Resident Duty Hour Restriction on Trauma Center Outcomes in Teaching Hospitals in the State of Pennsylvania

Abstract: Decreases in mortality and LOS during the study periods were likely not related to resident work hour restriction but rather to overall improvement in outcomes seen at Level II (no residents) and Level I (residents) TCs. Resident work hour restrictions had no discernible effect on patient care (noninferiority).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Two studies with mortality information were published after September 200935, 36. Addition of these two studies to the meta‐analysis resulted in the same mortality odds ratio in the QE model (1·28) but a widening of the c.i.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies with mortality information were published after September 200935, 36. Addition of these two studies to the meta‐analysis resulted in the same mortality odds ratio in the QE model (1·28) but a widening of the c.i.…”
Section: Discussionmentioning
confidence: 99%
“…The PTOS data include all trauma patients who are admitted for longer than 48 hours, intensive care unit admission, transfer cases, and mortality cases. 11 The patients with solitary hip fracture, asphyxiation, drowning, hypothermia, or hyperthermia are excluded from PTOS data. Also burn patients were excluded from this study.…”
Section: Methodsmentioning
confidence: 99%
“…[2][3][4][5][6][7] By contrast, contradictory results have been demonstrated in the literatures of surgical subspecialty, including trauma. [6][7][8][9][10][11][12] To complement the workload uncovered by residents under the work-hour restriction, a large number of surgical program currently hire the advanced practice providers (APPs), physician assistant (PA) and nurse practitioner (NP). [13][14][15][16] A recent survey conducted by Pezzi et al 14 showed that 79% of general surgery program use APPs, and significant increase of the number of APPs after implementation of work-hour restriction.…”
Section: Introductionmentioning
confidence: 99%